Runoff hydrographs using Snyder and SCS synthetic unit hydrograph methods: A case study of ungauged watersheds of Imam Turki Bin Abdullah Royal Nature Reserve (ITBA) - Saudi Arabia - Al-Dughairi, Ahmed Abdullah (Journal of natural sciences, life and applied sciences, 2023)
Background: The estimation of surface runoff and discharge peak using the Snyder’s model and SCS Dimensionless UH (SCS-DUH) method are one of the best alternatives solutions appropriate for analyzing the hydrologic systems in the ungauged watersheds. These two methods were applied to estimate the discharge peak and design their hydrographs in the drainage basins of Royal Nature Reserve (Imam Turki Bin Abdullah) in Saudi Arabia. - Aims: To estimate the discharge peak by applying Snyder’s model and SCS-DUH method using the morphometric parameters deriving from the SRTM DEM30m and three rainstorms of 40, 50 and 60mm. - Methods: The estimation of discharge peak (Qp) using Snyder’s model was depended on the SRTM DEM30m outputs and the hydrology parameters of the duration (Td) of Unit Hydrograph (UH), time to peak (Tp), time base of the UH (Tb), UH width at 50% and 75% of the peak discharge. However, the estimation of the discharge peak by The SCS-DUH method was computed using the drainage area (A), the direct runoff (Qd) and the time to peak (Tp). The direct runoff was determined by the runoff ratio 0.20 of the unimproved areas, proposed by the Soil Conservation Service (SCS). But, the time to peak was computed using the average of the concentration time obtained from Johnstone-Cross and Dooge models. The hydrographs design was done by the time ratio method recommended by the SCS. - Results: The estimated discharge peak computed by Snyder’s model varies with a maximum of 93.4 to 2092.9 m3/s, an average of 61.1 to 1368.4 m3/s and a minimum of 28.7 to 644.0 m3/s in Al Shuwaiki and Khtal watersheds, respectively. The estimated discharge peak computed by SCS-DUH method was ranged from 21.5 to 482.3 m3/s for the rainstorm of 40mm in Al Suwayki and Khtal, respectively, from 28.5 to 602.9 m3/s for the rainstorm of 50mm and from 34.1 to 723.5 m3/s for the rainstorm of 60mm, in Um Nqy and Khtal, respectively. - Conclusion: The hydrology study of ungauged basins in Royal Nature Reserve (ITBA) shows the great potential of the integrated emplyement of GIS technics and the hydrology models to estimate the discharge peak and design their hydrographs.